Die erediens as fees of die fees as erediens?: n Andrew Murray pryswenner n kwarteeu later herlees - Wepener, Cas; Bartlett, Andr (Verbum et ecclesia, 2014)
Worship as feast or feast as worship? Re-reading an Andrew Murray prizewinner one quarter of a century later. The aim of this contribution is to bring the book Die erediens as fees into discussion with the surrounding culture almost one quarter of a century after its publication. The surrounding culture, we shall call, following Martin Stringer and his so-called discourse of globalisation and consumerism, the feast as worship service . Based on this discussion, our research question pertains to the value of Die erediens as fees for the field of Liturgical Studies today. An answer is attempted by, firstly, sketching the liturgical landscape as well as national and international liturgical-scientific developments in our day and, secondly, providing a liturgical-aesthetical exploration and positioning Die erediens as fees within these developments and exploration.